El Canguro Tiene Mama? - Carle, Eric; Mlawer, Teresa ([New York] : HarperCollins, 2002)
Presents the names of animal babies, parents, and groups; for example, a baby kangaroo is a joey, its mother is a flyer, its father is a boomer, and a group of kangaroos is a troop, mob, or herd.
Keywords: Animals -- Juvenile literature. -- Infancy; Animals -- Infancy; Spanish language materials